2006
DOI: 10.1158/0008-5472.can-06-1645
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cyclin D1– and Estrogen-Regulated Genes Contributing to Breast Carcinogenesis and Progression

Abstract: Tumors can become lethal when they progress from preinvasive lesions to invasive carcinomas. Here, we identify candidate tumor progression genes using gene array analysis of preinvasive and invasive tumors from mice, which were then evaluated in human cancers. Immediate early response protein IEX-1, small stress protein 1 (HSPB8), and tumor necrosis factorassociated factor-interacting protein mRNAs displayed higher expression levels in invasive lesions than in preinvasive lesions using samples obtained by lase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 43 publications
5
80
0
Order By: Relevance
“…Previous studies demonstrated induction of Hsp22 by E 2 in ER ϩ breast cancer cells at the transcriptional level (Charpentier et al 2000;Yang et al 2006). Here, we present data concerning Hsp22 induction at the protein level.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…Previous studies demonstrated induction of Hsp22 by E 2 in ER ϩ breast cancer cells at the transcriptional level (Charpentier et al 2000;Yang et al 2006). Here, we present data concerning Hsp22 induction at the protein level.…”
Section: Discussionsupporting
confidence: 50%
“…The current hypothesis is that E 2 acts as an epigenetic factor that is involved in conversion of precancerous to cancerous cells in the course of tumor progression. Hsp22 was identified recently as a potential key player in the progression of breast cancer in humans (Yang et al 2006). Hsp22 expression is a downstream event of both erbB2 → cyclin D1 and E 2 signaling pathways, and this fact was suggested to be the basis for the well known association between cyclin D1 expression and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations